Decision‐making impairment under ambiguity but not under risk may underlie medication overuse in patients with chronic migraine - Lau, Chi Ieong; Chen, Wei‐Hung; Wang, Han‐Cheng; Walsh, Vincent (Headache, 2023)
Objective To explore whether patients with chronic migraine and medication overuse headache (CM + MOH) present with decision‐making deficit. Background Factors underlying MOH in patients with CM remain unclear. Whether the process of decision‐making plays a role in MOH is still controversial. Decision‐making varies in the degree of uncertainty: under ambiguity where the probability of outcome is unknown, and under risk where probabilities are known. Methods Decisions under ambiguity and risk were assessed with the Iowa Gambling Task and the Cambridge Gambling Task, respectively, whereas executive function was assessed by the Wisconsin Card Sorting Test. Results A total of 75 participants: 25 patients with CM + MOH, 25 with CM, and 25 age‐ and sex‐similar healthy controls (HCs), completed this cross‐sectional study. There was no significant difference in headache profiles except for more frequent analgesic use (mean ± SD: 23.5 ± 7.6 vs. 6.8 ± 3.4 days; p < 0.001) and higher Severity of Dependence Scores (median [25th−75th percentile]: 8 [5–11] vs. 1 [0–4]; p < 0.001) in patients with CM + MOH compared to CM. Total net score (mean ± SD) on the Iowa Gambling Task in patients with CM + MOH, CM, and HCs were − 8.1 ± 28.7, 10.9 ± 29.6, and 14.2 ± 28.8, respectively. There was a significant difference between the three groups (F(2, 72) = 4.28, p = 0.017), with patients with CM + MOH making significantly more disadvantageous decisions than patients with CM (p = 0.024) and HCs (p = 0.008), while the CM and HC groups did not differ (p = 0.690). By contrast, there was no significant difference between the groups in the Cambridge Gambling Task and the Wisconsin Card Sorting Test. Furthermore, performance on the Iowa Gambling Task was inversely correlated with analgesic consumption (r = −0.41, p = 0.003), suggesting that decision‐making under ambiguity may be related to MOH. Conclusions Our data suggest that patients with CM + MOH had impaired decisions under ambiguous, but not risky situations. This dissociation indicates disrupted emotional feedback processing rather than executive dysfunction, which may underlie the pathogenesis of MOH.